Dynamics of Mixed Dipterocarps Forests in Wanariset Semboja, East Kalimantan after Three Times of Forest Fires within the Periods of 1980-2003 - HERWINT SIMBOLON (Biodiversitas Journal of Biological Diversity, 2005)
A plot of 150x700 m2 was established in a mixed dipterocarps of Wanariset Semboja, East Kalimantan during the periods of 1979-1981. The forest was dominated by Eusideroxylon zwageri (Lauraceae), Dipterocarpus cornutus (Dipterocarpaceae), Pholidocarpus majadum (Arecaceae), and Diospyros borneensis (Ebenaceae). Since the plot establishment, the forests then had experienced three times of forest fires, those were in 1982-1983, 1994-1995 and 1997-1998. The present paper reports the results of re-measurement of some 150x110 m2parts of the plot in August 2003, about 23 years after plot establishment. Micro topographically, the studied plot was relatively undulating in higher parts and relatively flat in the lower parts of the plot, while the differences between lowest sub-plot and higher sub-plot of the remeasured plot was 26 m. Forest floor of the lower parts of the plot were humid to wet during rainy season and still humid during dry season. Almost all of the trees within lower parts of the plot were escaped from these three times of forest fires; hence these sub-plots weredominated by the trees of primary species that enumerated in 1980. Those sub-plots in the higher parts were burnt during the past forest fires indicated by the charcoal of standing trees and remaining felling logs in the forest floor. These burnt sub-plots were dominated by pioneer or secondary tree species, such as: Mallotus spp., Macaranga spp., Ficus spp. and Vernonia arborea. Local distribution of some indicator species (such as primary tree species: Pholidocarpus majadum, Diospyros spp., Eusideroxylon zwageri and species of Dipterocarpaceae; pioneer or secondary tree species Vernonia arborea, Macaranga spp., Mallotus spp., Ficus uncinulata, Piper aduncum, Peronema canescens) within the plot were figured. Mortality, recruitment and growth rate during the period of 1980-2003 were also discussed.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: dynamics, mix dipterocarps forest, forest fires, mortality, recruitment and growth rate.